2006
DOI: 10.1007/s00586-006-0142-8
|View full text |Cite
|
Sign up to set email alerts
|

Transforaminal steroid injections for the treatment of cervical radiculopathy: a prospective and randomised study

Abstract: Steroid injections are often employed as an alternative treatment for radicular pain in patients with degenerative spinal disorders. Prospective randomised studies of the lumbar spine reveal contradictory results and non-randomised and most often retrospective studies of the cervical spine indicate pain reduction from steroid injections. No prospective randomised study on transforaminal steroid injections for the treatment of radicular pain in the cervical spine focusing on short-term results has been performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 35 publications
2
92
0
1
Order By: Relevance
“…Conversely, our results are in agreement with a randomized controlled study by Anderberg et al 23 These authors assigned 40 patients presenting with chronic cervical radiculopathy from degenerative spondylosis, with a mean duration of symptoms of 31 months, to receive 1 fluoroscopically guided TFSI. The treatment group received an injection of mepivacaine and methylprednisolone, while the control group received an injection of mepivacaine and saline.…”
Section: Discussionsupporting
confidence: 82%
“…Conversely, our results are in agreement with a randomized controlled study by Anderberg et al 23 These authors assigned 40 patients presenting with chronic cervical radiculopathy from degenerative spondylosis, with a mean duration of symptoms of 31 months, to receive 1 fluoroscopically guided TFSI. The treatment group received an injection of mepivacaine and methylprednisolone, while the control group received an injection of mepivacaine and saline.…”
Section: Discussionsupporting
confidence: 82%
“…These include the use of EMG, MR imaging, and preprocedural selective nerve blocks. 8,16,17 Patients in this practice present for treatment after undergoing a variety of diagnostic tools, including CT, MR imaging, and EMG. Patients do not receive diagnostic nerve blocks before epidural injection.…”
Section: Discussionmentioning
confidence: 99%
“…Perineural injections including trans-laminar and transforaminal epidurals, selective nerve root blocks may be performed under radiographic guidance. 22,23 However, there is little highquality evidence on the best non-operative therapy for radiculopathy, although it has been reported that a multi-modal approach may alleviate symptoms. 24 In the current case physical therapy and medication for pain were used but these conservative methods did not resolve the symptoms.…”
Section: Discussionmentioning
confidence: 99%